พัฒนาการความสัมพันธ์เชิงอำนาจทางเศรษฐกิจและการเมืองในวัฒนธรรมเพลงไทยสากล - สาทร ศรีเกตุ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This study attempt to explain the political and economic power relation in Thai popular music culture from the beginning of the musical genre to 2002. The study’s assumption is that the cultural sphere is the area of struggle to gain or maintain hegemonic power and for ones to reach to hegemonic status, is to gain both Political Economy, the predominate power in production process, and Political sociology, the predominate power in discursive practices arena. The questions of the study are 1) how the power structure in Thai popular music production process been until 2002, 2) how the power structure in discursive practices in Thai popular music culture been until 2002, and 3) how the power relation studied in 1) and 2) reveal to Thai political development especially in the realm of democratic progress. The finding of the study is that Thai state was the hegemonic power in Thai popular music culture until 1973. After that the music industry was formed and encouraged the capitalist to jumped in and got more power in the industry, but the power of the state didn’t weak down because state and capitalist were not appeared a rival but alliance that made both were the co-predominate power in Thai popular music culture. However resistances were constantly happened and got more stronger by the means of changing in technology that declined the dominate power of the capitalist and democratic trend that empowered the subordinated to presented themselves, including their musical identities. Overall, the declined of the hegemonic power in Thai popular music culture revealed Thai democratic development especially the democratic of differences acceptance.